Juegos tradicionales para el desarrollo socio-afectivo - Caisa Tipan, Fanny Carina (2016)
The present research work about “Traditional Games for the Development Socio-Affective” to perform covers various parameters that researchers will work with the time. For this Project the problem was acen, which is a fundamental part to carry out the Project mentioned above with the desire to provide adequate solutions to the difficulties found, to the solution of the various problems posed by this project will perform various activities that are mentioned in the specific objectives, activities and methodologies, in which not only the children will be the beneficiaries also parents, teachers and the whole community to gain knowledge of how their children can develop skills that have not been found, using different types of methodology and techniques in this project is very important to the methodologies that were used which allow to perform activities consistent with children’s needs in relation to the traditional games. Using several techniques suhas the interview, the survey and the observation sheet, which is of great help in the collection of information and the acquisition of results for the project, for the search of information were cited various authors which helps the development of skill through the games. It has been cited several authors that showed different scientific opinions on the development of the game in children, in this case “Semillitas” center of Initial education, always bearing in mind that the game is not only fun also children learn faster spontaneously and what is best without mental tiredness from a very early age, obtaining also conclusions and recommendations which will provide in detail reports about how the games ancestral have a learning privileged since this type of games are not very common in educational institutions, this type of games has shown great quantity of stimuli in the environment of children helping them to develop a sense of the protection, conservation and almost all the senses that a person has.